Mesure de résultats des travaux communautaires chez les jeunes contrevenants : l’I.É.R.T.C. - Carrier, Suzanne; Fortin, Daniel; Paquet, Danielle (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
The community work program is designed for young offenders between the ages of 12 and 17. Participants are allowed to make restitution for their delinquent acts by working a certain number of hours in a neighborhood organization. Aside from this work aspect, the program also aims at arriving at various short-term results that serve as indications of the program's impact on participants. The lack of instruments able to systematically collect data for this purpose led to the creation of the Community Work Evaluation Tool (CWET). Grounded in the objectives of the community work program, the CWET measures the process by which its 13 items were arrived at, its validation and its psychometric properties. The CWET is argued to be a valid tool for evaluating the effects of such a program. These effects fall along four areas: (1) the personal evolution of each participant; (2) the participant's commitment to the completion of the program; (3) relationships between participants; and (4) the participant's attitude and openness toward the community.